re3dragon – A Research Registry Resource API for Data Dragons - Florian Thiery; Allard W. Mees (Groma)
The re3dragon (REsearch REsource REgistry for DataDragons) FLOSS tool envisages two aims: first, publication of an archaeology related open extendable LOD resource catalogue including authority-data, thesauri, gazetteers, (space-) time gazetteers as well as typologies and domain-specific resources. 2nd, re3dragon offers an API for requesting distributed LOD resources, returning resources in a standardised JSON format based on JSKOS. The re3dragon is coded in JAVA and Open Source published on GitHub